Основні напрями модернізації змісту і форм підвищення кваліфікації вчителів природничо-математичних предметів в Україні з урахуванням досвіду Республіки Польща - Євтушенко, Наталія (Національний технічний університет "Харківський політехнічний інститут", 2020)
У статті досліджено особливості й відмінності змісту і форм підвищення кваліфікації вчителів природничо-математичних предметів у післядипломній освіті України й Республіки Польща. Проаналізовано результати дослідження за міжнародною програмою TALIS (The OECD Teaching and Learning International Survey – Міжнародне опитування викладання та навчання в ОЕСР (Організація економічного співробітництва та розвитку)) щодо показників професійного розвитку і вдосконалення вчителів обох країн. Автором запропоновано заходи щодо оновлення змісту й форм підвищення кваліфікації українських вчителів з урахуванням досвіду Польщі – перехід на короткострокові курси підвищення кваліфікації (розширення фахового модуля), організація тематичних курсів фахово орієнтованих дисциплін, запровадження курсів психолого-педагогічної допомоги, курсів іноземних мов та програм на внутрішньо шкільному рівні.

Тhe article examines the features and differences of the content and forms of advanced training of teachers of natural and mathematical subjects in postgraduate education in Ukraine and the Republic of Poland. The results of a study under the international program of TALIS (The OECD Teaching and Learning International Survey) on the indicators of professional development and qualification improvement of teachers in both countries are analyzed. The author proposes measures to update the content and forms of professional development of Ukrainian teachers, taking into account the experience of Poland – the transition to short-term teacher training courses (expansion of the professional module), the organization of thematic courses in professionally oriented disciplines, the introduction of psychological and pedagogical assistance courses, foreign language courses and programs at the n-school level.
Main directions of modernization of the content and forms of increasing the qualification of teachers of natural-mathematical subjects in Ukraine, taking into account the experience of the Republic of Poland
Keywords: післядипломна освіта; postgraduate education